Influence of Surface Roughness of Spiral Bevel Gear on Oil Film Life of Starved Elastohydrodynamic Lubrication - Huang Shangren Huang Pengpeng (Jixie chuandong)
Taking the tooth surface of spiral bevel gear after grinding as study object, according to the grinding principle of spiral bevel gear, the grinding mask of tooth surface is solved, and the life prediction equation of the elastohydrodynamic lubrication oil film is established. On basis of this， the influence of surface texture parameters and roughness amplitude on the oil film life of the elastohydrodynamic lubrication is analyzed，and the validity of the oil film life calculation model is verified by experiment. The results show that surface texture parameters of spiral bevel gear pair have minimal impact on the elastohydrodynamic lubrication oil film life, and within the scope of the calculation of roughness, the moderate improvement of gear surface roughness will be conducive to promoting the oil film life of the spiral bevel gear pair in the elastohydrodynamic lubrication phase.